PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DAN KEPUASAN PELANGGAN PADA RUMAH SAKIT SWASTA DI KOTA DENPASAR - Ayu Desi Indrawati (Faculty of Economics and Business Udayana University, 2013)
This study aimed to determine the effect of job satisfaction on employee performance, employee performance to customer satisfaction, and job satisfaction on customer satisfaction through employee performance. This study took place in hospitals-private hospital in Denpasar, sing hospital employees and patients as research respondents. Proof of this hypothesis using path analysis techniques.The results obtained in this study that are: 1) job satisfaction have significant positive impact on employeeperformance, 2) the performance of the employee significant positive effect on customer satisfaction, and 3) positively influence job satisfaction directly and indirectly through the employee’s performance to customer satisfaction.